2021
DOI: 10.3390/jmse9111168
|View full text |Cite
|
Sign up to set email alerts
|

A Wind–Wave-Dependent Sea Spray Volume Flux Model Based on Field Experiments

Abstract: Sea spray can contribute significantly to the exchanges of heat and momentum across the air–sea interface. However, while critical, sea spray physics are typically not included in operational atmospheric and oceanic models due to large uncertainties in their parameterizations. In large part, this is because of the scarcity of in-situ sea spray observations which prevent rigorous validation of existing sea spray models. Moreover, while sea spray is critically produced through the fundamental interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Equation (2) assumes that the sea spray droplets are perfect geometrical globes, and the radius of all sea spray droplets are within a specific range (30 µm < r < 500 µm) [17,18]. Based on unique in situ sea spray observations, Xu et al [19] proposed one novel nondimensional wave-steepness-dependent sea spray model to determine sea spray volume flux, given by…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (2) assumes that the sea spray droplets are perfect geometrical globes, and the radius of all sea spray droplets are within a specific range (30 µm < r < 500 µm) [17,18]. Based on unique in situ sea spray observations, Xu et al [19] proposed one novel nondimensional wave-steepness-dependent sea spray model to determine sea spray volume flux, given by…”
Section: Introductionmentioning
confidence: 99%
“…Based on the field measurement of Humidity Exchange Over the Sea (HEXOS), α, β and γ are 1.5, 10.5 and 0.2, respectively [5]. Using Equations ( 4)-( 8), the wave-Reynolds-dependent sea spray model of Zhao, Toba, Sugioka and Komori [17] and the wave-steepness-dependent sea spray model of Xu, Voermans, Ma, Guan and Babanin [19] can be used to estimate the contribution of sea spray to the air-sea heat fluxes, and can be included in the TC forecasting model. In this study, we aim to investigate the thermal effects of the aforementioned sea spray models on the local atmosphere, wave, and ocean fields under an idealized TC system.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, as the parameterization of Xu, Voermans, Ma et al (2021) is developed based on field observations of laser backscatter, uncertainties may exist due to the modulation of laser attenuation by sea surface roughness properties as discussed by Xu, Voermans, Ma et al (2021). Though further validation is required using laboratory, field and numerical observations, it is promising that this spray model, even when extrapolated to higher wind speeds, is well aligned with current sea spray models in both trend and magnitude (Xu, Voermans, Ma, et al, 2021). We further note that the extrapolation of sea spray models to extreme weather conditions in numerical models, as implied by Zhao et al (2017) and Prakash et al (2019), is commonly used and markedly improves the TCs modeling.…”
Section: Discussionmentioning
confidence: 99%
“…where U 10 is the 10 m height WSP; s = H s k m /2 is the mean wave steepness, H s is the significant wave height, and given at deep and shallow water k m = (2πf m ) 2 /g and 𝐴𝐴 𝐴𝐴𝑚𝑚 = 2𝜋𝜋𝑓𝑓𝑚𝑚∕ √ gh is the mean wave number, respectively, where the f m is the mean wave frequency and the g is the acceleration gravity. Using field observations of laser backscatter to parameterize the sea spray model, the model of Xu, Voermans, Ma et al (2021) was found to perform remarkably similar to the model of Andreas (1992), both in trend and magnitude, when compared against the mean WSP. Notably different, however, is that the model of Andreas (1992) does not explicitly depend on the properties of the wave field.…”
mentioning
confidence: 82%
“…6g-l). This provides a condition unfavorable for sea spray generation, because of the reduction of both wind forcing and wave breaking (Xu et al 2021a). Thus, it has negative feedback on intensification for a larger TC since an increase in sea spray is known to increase the sea-air enthalpy transfer (Andreas and Emanuel 2001;Bao et al 2011;Wang et al 2001;Xu et al 2021b).…”
Section: Roles Of Ocean Wavesmentioning
confidence: 99%